Quality of surface water in the steppe zone of the river basin Zhayik (Journal of Geography and Environmental Management, 2018)
Water is the main strategic resource of any nation. Condition of water systems in particular, is reduced due to man-made impact. The main source of water pollution are the objects of production centers. Also, the development of agriculture affects to water pollution, it can be seen in the intensive use of pesticides and substances for plant conservation. Remains of municipal services also pollutes the water to some extent. All of the above factors perform an important role in determining the monitoring of natural water objects. The purpose of this article to learn how to identify the quality of surface waters, identifying the source of contamination, determine the quality of the objects of water on areas of the test pool. This article covered hydrochemical indices of 14 water objects in the river basin Zhaiyk. A description of these objects was given by the physical condition, and in the result it was evaluated quality of water polluting substances in quantitative indices. Water quality is described in the state standard 3351-74 and StateStandard 26449.1-85. Surface water pollution level was evaluated by 17 components and identify the sources of water pollution.